Perancangan User Experience Aplikasi Pemesanan Water Tank di Kota Kupang menggunakan Metode Human Centered Design - Alexandrio Kharisma Putra Marasin; Ratih Kartika Dewi; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Kupang is one of the cities experiencing the impact of water shortages in Indonesia. This problem has arisen for many years because water sources in the city are pretty limited. Therefore, many from the private sector are developing clean water service businesses by utilizing underground water (bore well water with a depth of > 80 m) distributed to households using water tankers. However, bore healthy water entrepreneurs have difficulty selling their water to water tank car owners. This is because most of the people of Kupang City do not know about the existence of a water tank car taken from several borehole waters in Kupang City. In addition, from a customer perspective, it is also challenging to get clean water. The application design for ordering water tanks in the city of Kupang is carried out using an approach, namely the Human-Centered Design method. This method is very appropriate in this study because it is directly centered on the user. The application is in the form of mobile using the operating system in the form of Android. At the testing stage, it was carried out using the usability testing method on ten respondents with a background of being tank water customers in Kupang City. Furthermore, the usability value in the effectiveness aspect is 90%, in the efficiency aspect, it is 0.076 goals/sec, and finally in the user satisfaction aspect it is 82 which is category A. Then, at the last stage, re-evaluation is carried out in order to get the maximum results that the user can accept.